YAPILANDIRMACI ÖĞRENME KURAMINA DAYALI ÖĞRETİM UYGULAMALARININ 6. SINIF SOSYAL BİLGİLER DERSİ KONULARININ ÖĞRETİMİNE ETKİLERİ - (:unkn) unknown (My University, 2013)
Bu araştırmanın amacı yapılandırmacı öğrenme kuramına dayalı öğretim uygulamalarının ilköğretim 6. sınıf Sosyal Bilgiler dersi konularının öğretimi üzerine etkilerini ortaya koymaktır. Bu amaçla yapılandırmacı öğrenme kuramı Sosyal Bilgiler dersinde eğitim durumlarına uygulanarak öğrencilerin derse yönelik tutumları, erişi ve kalıcılık düzeyleri tespit edilmeye çalışılmıştır. Araştırmada nicel ve nitel araştırma yöntemlerinin birlikte kullanıldığı üçgenleme (triangulation) modeli kullanılmıştır. Nicel araştırma yöntemlerinden yarı deneysel model ile nitel araştırma yöntemlerinden durum çalışması seçilerek üçgenleme modellerinden yöntem üçgenlemeye karar verilmiştir. Yarı deneysel modelde elde edilen veriler t testine, durum çalışmasında elde edilen veriler ise betimsel analiz ve içerik analizine tabi tutulmuştur. Araştırma, 6. Sınıfta öğrenim gören iki 1şubenin öğrencileri (N=66) ile gerçekleştirilmiştir. Öğrencilere derse ilişkin tutumlarını belirlemek için dönem başında ve dönem sonunda Sosyal Bilgiler Dersi Tutum Ölçeği ve Standartlaştırılmış Görüşme Formu, erişi ve kalıcılık düzeylerini belirlemek için ise her üniteye başlamadan önce ve her ünite bittikten sonra başarı testi ve 2N formları uygulanmıştır. Araştırma sonucunda, yapılandırmacı öğrenme kuramına dayalı olarak düzenlenen Sosyal Bilgiler dersi öğretim uygulamalarının öğrencilerin derse yönelik tutumlarına, erişi ve kalıcılık düzeylerine olumlu bir etki yaptığı görülmüştür

The aim of this study is to determinate the effects of the constructivist learning theory grounded activities on teaching 6th grade social studies course issues. In parallel with this, educational contexts were constructed depended on the constructivist learning theory and effects of these exercises on attitude, achievement and permanence levels were assessed. Triangulation which was a research design that combines the qualitative and quantitative methods was used in this study for the aim of getting reliable, in depth and detailed data. Quantitative analyze methods and qualitative analyze methods were used together in this research. Attitude scale and achievement tests were applied both to research and control groups as pre-test and post-test. The universe of this study was consisted of 6th grade students which were attending to primary schools in Kadıköy-Istanbul during 2005-2006 school years. 66 students in 6/A and 6/B classes of Ihsan Sungu Primary School in Kadıköy formed the sample group of this research. "Likert type attitude scale" was developed to evaluate the effect of activities grounded on constructivist learning theory on students' attitudes towards Social Studies course. Achievement tests were developed to determinate the effects of constructivist learning theory grounded activities on students' achievement and permanence level, "2N (What did I know? - What did I learn?) forms were formed to assess the mean differentiation in detailed and, individual and group worksheets were developed as data collection tools. It was determined that Social Studies courses based on constructivist learning theory had positive effect on students' attitudes towards this course, achievement and permanence levels when we compared it with traditional teaching practices.
(The Effects on Subjects of Social Studies Lesson of Instructional Practices Based Constructivist Learning Approach)
Keywords: Matematik; Eğitim, Eğitim Araştırmaları; Müzik